Land use/ land cover change and its impact on soil erosion process in Begnas Tal Rupa Tal watershed using geospatial tools, Kaski district, Nepal - Koirala, Saroj (2010)
Dissertation submitted in partial fulfilment of the requirements for the Degree of Master of Science in Geospatial Technologies